Frequency-domain control design for high-performance systems - O'Brien, John, 1968 July 16- (IET control engineering series ;, 2012)
This book serves as a practical guide for the control engineer, and attempts to bridge the gap between industrial and academic control theory. Frequency domain techniques rooted in classical control theory are presented with new approaches in nonlinear compensation that result in robust, high-performance closed-loop systems. Illustrative examples using data from actual control designs are included.